2019
DOI: 10.1093/reseval/rvz023
|View full text |Cite
|
Sign up to set email alerts
|

European Research Council: excellence and leadership over time from a gender perspective

Abstract: European Research Council Grants (ERC) have become the most important vehicle for funding scientific research in the EU. Since their creation in 2007, they have provided funding for around 7,000 of the nearly 70,000 proposals for research projects submitted. With a success rate of about 11%, these Grants are highly competitive. Despite major advancement of women’s participation in research activity, women overall remain the minority in Science, Technology, Engineering and Mathematics (STEM disciplines). Agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 78 publications
(60 reference statements)
1
8
0
1
Order By: Relevance
“…But, in the case of those who applied to over 6 competitions, the difference is significant in favour of men. These results confirm a part of our third hypothesis, and are in line with the results of other studies in the literature [15,23,24,29,30] that also point out that women apply less than men in research funding competitions.…”
Section: Plos Onesupporting
confidence: 92%
See 1 more Smart Citation
“…But, in the case of those who applied to over 6 competitions, the difference is significant in favour of men. These results confirm a part of our third hypothesis, and are in line with the results of other studies in the literature [15,23,24,29,30] that also point out that women apply less than men in research funding competitions.…”
Section: Plos Onesupporting
confidence: 92%
“…Another issue is the idea that women apply less [15,23,24], and as a consequence, they succeed less often [15,16,[25][26][27]. Deriving from here is the fact that this could be one of the key causes for women having less successful scientific careers [28].…”
Section: Plos Onementioning
confidence: 99%
“…An analysis of research grants from the Wellcome Trust, a major funder in the UK, showed that fewer women applied for grants, and those were awarded received much smaller grants on average than did men during 2000 and 2008 (Bedi et al, 2012). Similar grant-seeking gender disparity was observed for the Canadian Institutes of Health Research (CIHR) Foundation (Burns et al, 2019;Witteman et al, 2019a), the US National Institutes of Health (NIH), and NSF (Pohlhaus et al, 2011;Hechtman et al, 2018;Grogan, 2019), and across Europe (Watson and Hjorth, 2015;Bautista-Puig et al, 2019). For example, in Denmark, even taking into account of the "Younger women Devoted to a UNiversity career" (YDUN) research awards, male principal investigators on average still received a greater grant amount than their female colleagues (Watson and Hjorth, 2015).…”
mentioning
confidence: 85%
“…Research Council Starting Grants, Consolidator Grants or Advanced Grants from 2007 to 2016 was consistently lower than the success rate of men. 9 Other factors than gender can influence peer review. A study of the Australian Research Council found that applicant-nominated reviewers tended to give better ratings than panel-nominated reviewers.…”
Section: Open Accessmentioning
confidence: 99%
“… 8 Finally, the success rate of women applying for European Research Council Starting Grants, Consolidator Grants or Advanced Grants from 2007 to 2016 was consistently lower than the success rate of men. 9 …”
Section: Introductionmentioning
confidence: 99%